Separation of Anionic Chlorinated Dyes from Polluted Aqueous Streams Using Ionic Liquids and Their Subsequent Recycling - Kamenická, Barbora; Švec, Petr; Weidlich, Tomáš (International journal of molecular sciences, 2023)
The effect of ionic liquids on the separation of chlorinated anionic dyes such as Mordant Blue 9 (MB9) or Acid Yellow 17 (AY17) via ion exchange has been investigated in model aqueous solutions that simulate wastewater from the textile dyeing industry. The effect of ionic liquids chemical nature on the separation efficiency of mentioned dyes has been compared. It was found that especially ionic liquid based on quaternary ammonium salts comprising two or three long alkyl chains bound to the quaternary ammonium nitrogen (typically benzalkonium chloride or Aliquat 336) are very effective for the separation of both studied MB9 and AY17 from aqueous solution. In addition, the innovative technique has been developed for the reactivation of spent ionic liquids which is based on the chemical reduction of the formed ion pairs using NaBH4/NiSO4, NaBH4/Na2S2O5 or Raney Al-Ni alloy/NaOH. Thus, only NaBH4/NiSO4 in co-action with Al-Ni alloy enables both effective reduction of the azo bond and subsequent hydrodechlorination of emerging chlorinated aromatic amines. The efficiency of tested dyes separation or regeneration of ion pairs was evaluated by determination of the absorbance at wavelength of the maximum absorbance, of the Chemical Oxidation Demand (COD), and of the Adsorbables Organically bound Halogens (AOX). The formation of ion pairs or products of reduction and hydrodechlorination of these ion pairs has been studied using the 1H NMR and LC-MS techniques.
Keywords: Coloring Agents; NaBH4; ion pairs; Mordant Blue 9; acid azo dye; ionic liquids; hydrodechlorination; aminy; Wastewater; azosloučeniny; Amines; iontové kapaliny; barvicí látky; dehalogenation; Azo Compounds; Ionic Liquids; odpadní voda; reduction; Acid Yellow 17; NiSO4; Raney Al-Ni alloy